2008
DOI: 10.5551/jat.e532
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin Decreases Plasma Pre.BETA.1-HDL Concentration and Might Promote its Disappearance Rate in Hypercholesterolemic Patients

Abstract: Aim: Pre 1-HDL is involved in the initial step of cholesterol efflux from peripheral cells and plays an important role in reverse cholesterol transport. We studied the effect of pitavastatin on the HDL subfraction profile, pre 1-HDL concentration and its disappearance rate. Methods: Twenty-nine hypercholesterolemic patients were treated with pitavastatin at 2 mg/day for 4 weeks, and plasma levels of total cholesterol (TC), triglyceride, HDL-cholesterol (C), HDL2-C, HDL3-C, pre 1-HDL, LCAT activity, and CETP ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
1
22
1
5
Order By: Relevance
“…It is known that when plasma is incubated at 37°C, the concentration of plasma pre ␤ 1-HDL decreases and this decrease is blocked by the presence of DTNB ( 10,21,45,47 ). Although the mechanism has not yet been clarifi ed, the phenomenon seems to be a LCAT-dependent effect because it has been reported that the same effect is shown when anti-LCAT antibody is used instead of DTNB ( 47 ), and that plasma LCAT activity is positively correlated with the decreased level of plasma pre ␤ 1-HDL in the experiment ( 25 ). In the present study, lipid-free apoA-1 added to pre ␤ 1-HDL-depleted plasma showed the same variation in concentration as plasma pre ␤ 1-HDL in a LCAT-dependent manner ( Fig.…”
Section: Epitope Of Anti-apoa-1 Mabsmentioning
confidence: 90%
See 1 more Smart Citation
“…It is known that when plasma is incubated at 37°C, the concentration of plasma pre ␤ 1-HDL decreases and this decrease is blocked by the presence of DTNB ( 10,21,45,47 ). Although the mechanism has not yet been clarifi ed, the phenomenon seems to be a LCAT-dependent effect because it has been reported that the same effect is shown when anti-LCAT antibody is used instead of DTNB ( 47 ), and that plasma LCAT activity is positively correlated with the decreased level of plasma pre ␤ 1-HDL in the experiment ( 25 ). In the present study, lipid-free apoA-1 added to pre ␤ 1-HDL-depleted plasma showed the same variation in concentration as plasma pre ␤ 1-HDL in a LCAT-dependent manner ( Fig.…”
Section: Epitope Of Anti-apoa-1 Mabsmentioning
confidence: 90%
“…We previously obtained a monoclonal antibody (MAb) 55201 (MAb55201) that specifically recognizes apoA-1 in pre ␤ 1-HDL and developed an ELISA for easily measuring plasma pre ␤ 1-HDL concentrations using the MAb ( 21 ). Recently a variety of research results on pre ␤ 1-HDL using the ELISA were reported, in particular the relationships between plasma pre ␤ 1-HDL concentrations and coronary artery disease and medications have been noted (22)(23)(24)(25)(26).…”
Section: Purifi Cation Of Plasma Pre ␤ 1-hdlmentioning
confidence: 99%
“…Several clinical trials have reported that aggressive lipid-lowering therapy not only suppresses the progression of atherosclerosis, but also contributes to its regression. [9][10][11] Although the administration of rosuvastatin and atorvastatin resulted in a significant regression of coronary atherosclerosis 12 and significantly increased HDL-C levels, [12][13][14][15][16] the effects of statins on the 3 stages of RCT in vivo have not yet been reported. We hypothesized that these strong statins might promote the expression of several factors involved in RCT independent of lowering LDL-C, and there might be differences in the effects of rosuvastatin and atorvastatin on RCT.…”
mentioning
confidence: 99%
“…This may simply reflect the effects of lipid-lowering drugs, because statins also decrease CETP mass in hypercholesterolemic patients [12]. Alternatively, ezetimibe may regulate the CETP gene at transcriptional levels.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…We recently reported that pitavastatin decreases CETP mass and LCAT activity in hypercholesterolemic patients [12]. Furthermore, genome-wide association studies involving >100,000 individuals of European ancestry identified LCAT and CETP as significantly associated loci with plasma HDL-C [13].…”
mentioning
confidence: 99%